2004
DOI: 10.1002/app.20207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compatibilization of oxidized polypropylene on PP blends of PP/PA6 and PP/talc

Abstract: ABSTRACT:The influence of compatibilization on the dynamic mechanical properties of polypropylene (PP) binary blends with polyamide-6 (PA6), Talc, and oxidized PP (OPP) was investigated. The oxidation of PP homopolymer was performed in a internal mixer by using air as a oxidizing agent (under atmospheric pressure) and dodecanol-1 as an accelerator at 180°C for 6[1-2] h [Abdouss, M.; Sharifi-Sanjani, N.; Bataille, P. J Appl Polym Sci 1999, 36, 10]. In the blends, OPP was used as a blend component and compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It was interesting to find that the crystallization peaks of PA11 at high temperature (165.6°C) became weak, while those peaks at low temperature (≈100°C) turned into more apparent. This phenomenon was regarded as the typical confined crystallization, and it was common in immiscible polymer blends with dispersed phases, especially in the crystalline/amorphous immiscible polymer blends with "sea-island" structures such as PA6, iPP, LLDPE, and PEO [22][23][24]. It was also reported that PA11, as a dispersed phase, underwent supercooling during the cooling process.…”
Section: Melting and Crystallizationmentioning
confidence: 99%
“…It was interesting to find that the crystallization peaks of PA11 at high temperature (165.6°C) became weak, while those peaks at low temperature (≈100°C) turned into more apparent. This phenomenon was regarded as the typical confined crystallization, and it was common in immiscible polymer blends with dispersed phases, especially in the crystalline/amorphous immiscible polymer blends with "sea-island" structures such as PA6, iPP, LLDPE, and PEO [22][23][24]. It was also reported that PA11, as a dispersed phase, underwent supercooling during the cooling process.…”
Section: Melting and Crystallizationmentioning
confidence: 99%
“…This increment in thermal resistance can be attributed to the reduction of the third type hydrogen and formation of carboxylate salts (COO-N+Me3Ph) in oxidized polypropylene (Abdouss et al 1999). Moreover, it is inferred from DTA diagram that the amount of the released heat from polypropylene is higher than oxidized polypropylene; in other words, oxidized polypropylene acts as an insulator preventing exodus energy emerging and finally produces less energy while burning (Abdouss et al 2004). …”
Section: Thermal Analysis Of Oxidized Polypropylenementioning
confidence: 99%
“…There are very few studies where a quite fine dispersion of the minor phase in the matrix can be achieved by using ionomers, polypropylene-grafted-acrylic acid, ethylene-butylene acrylate-grafted-fumaric acid, ethylene-ethyl acrylate-glycidyl methacrylate as compatibilizers [12][13][14]. Unfortunately, the MAH is toxic and of low boiling point, and it is difficult to prepare PP-g-MAH, which limits the application of PP-g-MAH as a compatibilizer for the immiscible blends such as PP/PA6.…”
Section: Introductionmentioning
confidence: 99%